Correlation Between the Severity of Dry Eye Disease and Fluorescein Break-Up Patterns (FBUP) - Petty Purwanita; Putri Dwi Kartini (Sriwijaya Journal of Medicine, 2023)
Dry eye disease is a disorder of the eye surface characterized by instability of the tear film. The FBUP examination is one of the examinations used to determine the stability of the tear film. The various symptoms that occur in each type of dry eye indicate differences in break-up patterns (BUP). This study aims to determine the correlation between the severity of dry eye disease and the appearance of FBUP at RSUP dr. Mohammad Hoesin Palembang. A correlative analytical cross-sectional study was undertaken at the Eye Polyclinic, Infection- Immunology Subdivision, Dr. Mohammad Hoesin General Hospital Palembang from January to June 2022. There were 32 patient samples with 60 dry eye samples that met the inclusion criteria. The correlation between the Schirmer Test, TBUT and the severity of dry eye disease with the appearance FBUP was analyzed using the Spearman Rho's test. All data were analyzed with SPPS version 23.0. In this study, the results showed that there was a moderate and significant positive correlation between the degree of the Schirmer test and the appearance FBUP (r = 0.482; p = 0.000) and a moderate and significant positive correlation between the TBUT degree and the appearance FBUP (r = 0.435; p = 0.001) . In addition, the results showed that there was a moderate and significant positive correlation between the severity of dry eye disease and the appearance of FBUP (r = 0.478; p = 0.000). Using the multivariate test, it was concluded that the degree of dry eye was statistically significantly related to age (p = 0.001) and gender (p = 0.001). There is a correlation between the severity of the disease and the appearance FBUP of patients with dry eye disease.